Opera omnia Desiderii Erasmi Roterodami: recognita et adnotatione critica instructa notisque illustrata / Ordo 1, Tomus 2 - Erasmus, Desiderius (Opera omnia Desiderii Erasmi Roterodami recognita et adnotatione critica instructa notisque illustrata, 1971)
Inhalt: Preface -- De pueris statim ac liberaliter instituendis, ed. Jean-Claude Margolin - De ratione studii, ed. Jean-Claude Margolin - De conscribendis epistolis, ed. Jean-Claude Margolin - Dialogus Ciceronianus, ed. Pierre Mesnard - Liste des abreviations, Index nominum. - This volume of the Amsterdam edition of the Latin texts of Erasmus deals with education and learning, and the mastery of Latin. It presents a critical edition of the Latin texts of De pueris instituendis, De ratione studii, De conscribendis epistolis and Ciceronianus. The Latin text is clarified by introductions and notes in French, which offer linguistic, historical and philological background information clarifying the text. (Verlagsinformation)